The Effect of Corporate Governance on Earnings Management - RORENG, PETRUS PELENG (The journal of contemporary issues in business and government, 2021)
This study aimed to examine the effect of corporate governance on earnings management. Independent variables used in this study are the proportion of independent board, audit committee, the structure of managerial ownership and institutional ownership structure. The ratio of independent commission was measured to study the percentage of the number in the independent board t o entire board of commissioners in the company. Audit committee in this research do, that was calculated by adding up the audit committee in the company. The managerial ownership structure is measured by the percentage of shares owned by managers of the total shares outstanding. The institutional ownership structure is measured by the percentage of shares owned by the institutions of the total shares outstanding. Earnings management as the dependent variable proxied by discretionary accruals and is calculated by the modified Jones model. This research was conducted using data from documentation using www.idx.co.id, Indonesian Capital Market Directory (ICMD). The method of analysis used in this study is multiple linear regressions. This study used a sample of manufacturing firms listed on the Indonesia Stock Exchange (IDX) 2013-2016. The results showed the simultaneous variable proportion of independent board, audit committee, the structure of managerial ownership and institutional ownership structure have a significant effect on earnings management. However, only the precarious balance of independent board is a substanti a l effect on earnings management.